(untitled) (University Heart Journal, 2025)
Background:Trigyceride-glucose (TyG) index is a composite indicator composed of triglyceride (TG) and fasting blood glucose (FBS). It is a simple, reliable and easily accessible marker of insulin resistance (IR) which is associated with different metabolic and cardiovascular diseases (CVD) including coronary artery disease (CAD). Objective: To investigate the correlation between the TyG index and cardiovascular risk factors, and the predictive value of TyG index with severity of CAD assessed by SYNTAX score. Methods: This cross-sectional analytical study was done in the Department of Cardiology, Bangladesh Medical University, Dhaka, Bangladesh, from January 2025 to June 2025 including a total of 50 patients undergoing coronary angiogram (CAG) during the index hospitalization. The TyG index was calculated as Ln [fasting triglyceride (mg/dL) ×fasting glucose (mg/dL)]/2. Linear regression analysis were done to assess relationship between cardiovascular risk factors and TyG index. The severity of CAD was assessed by the SYNTAX score and logistic regression analysis was done to assess predictive value of TyG index with severity of CAD. Results: On the basis of median TyG index level level (9.33) study population were divided into two groups (low TyG index and high TyG index). In univariate linear regression analysis showed positive relation of TyG index with male gender (p=0.039), diabetes mellitus (p<0.001), dyslipidaemia (p=0.004), FBS (p=0.008) and TG/HDL ratio (p<0.001). Multivariate linear regression analysis further indicated diabetes mellitus (p=0.002) and TG/HDL ratio (p<0.001) were independently associated with TyG index. ROC curve analysis revealed strong relationship between TyG index and intermediate to high SYNTAX score with AUC of 0.799 and cut of value 9.53 yielded a sensitivity of 75.0% and a specificity of 76.5%.In univariate logistic regression analysis showed smoking (p=0.012) and TyG index (p=0.017) were significant predictors of intermediate to high SYNTAX score(≥23). On multivariate logistic regression analysis also showed TyG index (p=0.034) was independent predictor of intermediate to high SYNTAX score. Conclusion: TyG index has strong correlation with different clinical risk factors like male gender, diabetes mellitus, dyslipidemia. TyG index may be considered as independent predictor of intermediate to high SYNTAX score. As it is a simple, easily accessible and inexpensive marker, it can be used for risk stratification before CAG to assess severity of CAD. University Heart Journal 2025; 21(2): 75-80